Italian Journal of Pediatrics - Caffarelli, Carlo; Santamaria, Francesca; Corsello, Giovanni
The Italian Journal of Pediatrics includes all aspects of pediatric medicine and also covers health service and public health research that addresses primary care issues. The journal provides a high-quality forum for pediatricians and other healthcare professionals to report and discuss up-to-the-minute research and expert reviews in the field of pediatric medicine.